An Analysis of Error in Narrative Text for The 11th Grade Students - Novianti Sola Skriptura; Ch Evy Tri Widyahening; Ayu Istiana Sari (English Education Department Slamet Riyadi University Surakarta, 2021)
The objectives of the research were: (1) to find out the types of errors that occursed on the use of Simple Past Tense in English Narrative Text written by the Eleventh Grade Students of SMK Kristen 1 Surakarta in Marketing Business Class in 2019/2020 Academic Year, and (2) to find out the cause of errors on the use of Simple Past Tense in English Narrative Text written by the Eleventh Grade Students of SMK Kristen 1 Surakarta in Marketing Business Class in 2019/2020 Academic Year. Error analysis is a method used to document the errors that appear in learner language, determine whether those errors are systematic, and explain what caused them. The method of this research was a qualitative research. In this study the researcher observed and analyzed the data. The researcher analyzed the data, data collecting methods and its instruments that applied by the researcher in this research were Interview, Observation, and Documentation. The results of this study showed that type of errors which made by the students in a story entitled ‘Malin Kundang’ was Omission, with total percentage was 15%, Addition with total percentage was 10%, Misinformation with total percentage was 62%, and Misordering with total percentage was 14%. In a story entitled ‘The White Snake’ is Omission with total percentage was 13%, Addition with total percentage was 4%, Misinformation with total percentage was 52%, and Misordering with total percentage was 30%. In a story entitled ‘The White Lady’ is Omission with total percentage was 9%, Addition with total percentage was 4%, Misinformation with total percentage was 74%, and Misordering with total percentage was 13%. The results of the research showed that after conducting the test to writing of Simple Past Tense in Narrative Text, it was found that most students (62% in a story entitled ‘Malin Kundang’, 52% in a story ‘The White Snake’ and 74% in a story entitled ‘The White Lady’) made errors in the misinformation. It was happened because students did not know about changing of verb 1 to verb 2 and this happens because some students were still confused about the used of the Simple Past Tense in Narrative Text. Keywords: Error Analysis, Simple Past Tense, Narrative Text, and Marketing Business